Risk management in international grain trade under martial law in Ukraine - Rekachynskyi, Denys (Здобутки економіки: перспективи та інновації, 2025)
Ukraine’s role as a major global grain exporter was critically challenged by the full-scale war and the introduction of martial law, which generated complex economic, logistical and institutional risks in international grain trade. Blocked ports, disrupted supply chains, and heightened uncertainty reshaped export operations and created an urgent need to reassess approaches to risk management under extreme conditions. Purpose of the article is to identify the economic risks that emerged in Ukraine’s international grain trade during 2022–2025 under martial law and to analyse the mechanisms applied by state institutions, businesses, and international partners to manage these risks. Methods. The study applies a systemic analytical approach to evaluating the risk structure in international trade, comparative analysis of export dynamics in pre-war and wartime periods, and case analysis of Ukrainian exporters and institutional responses. Statistical and structural-dynamic analyses are based on data from USDA, the Ministry of Agrarian Policy of Ukraine, the EU and specialized reports. Results. The war generated a multilayered crisis in grain exports, including infrastructure destruction, port blockades, financial instability, regulatory obstacles and market disruptions. Wheat exports in 2022–2023 declined by nearly 20%, while corn exports fell by about 5% due to logistical prioritization. A set of risk-mitigation measures was implemented at multiple levels: the Black Sea Grain Initiative, EU “solidarity lanes,” international insurance programmes, price-hedging tools, and financial guarantees from EBRD and ECAs. These combined instruments enabled a recovery to almost pre-war export volumes (48.7 million tons) by 2023. Conclusions. Effective risk management during wartime required a combination of diplomatic, financial and logistical mechanisms involving the state, business and international partners. The obtained results provide a foundation for shaping policies aimed at diversifying export infrastructure, strengthening military-risk insurance tools, developing exchange-based hedging instruments for agricultural markets, and increasing the resilience of supply chains. For businesses, the findings highlight the importance of flexible, integrated risk-management models that incorporate financial, logistical and institutional tools in conditions of prolonged instability.